Herramientas digitales para el aprendizaje del idioma kichwa en sexto grado de la Unidad Educativa Comunitaria Intercultural Bilingüe Mushuk Rimak, Loja 2024 - Zhondo Macas, Anabell Alexandra (2024)
Kichwa was considered a language franca, used for years before the arrival of the Spanish, unfortunately, it is at risk of disappearing, possibly due to the lack of initiatives that promote its learning and preserve a culture essential for identity. This is why this research, titled Digital Tools for Learning the Kichwa Language in the Sixth Grade of the Mushuk Rimak Intercultural Bilingual Community Educational Unit, Loja 2024, has the general objective: Determine the impact of digital tools through a didactic proposal for the learning of the Kichwa Language in sixth-grade students of the Mushuk Rimak Intercultural Bilingual Community Educational Unit, Loja 2024. The research adopts a mixed approach with a quasi-experimental design and a descriptive study, to carry out the research, using the following methods: Hermeneutic, inductive, deductive, analytical, synthetic, and statistical, which contributed to the analysis and understanding of the research. The studied population consisted of 15 students and two teachers. To know the initial level of the students, a diagnostic evaluation was carried out, while structured interviews were carried out for the teachers. The initial results showed that 100% of the students did not achieve the required learning. The didactic proposal "Yachay wiñay" effectively achieved significant learning by diversifying teaching strategies. It was evident that 7% of the students were close to achieving the required learning, 20% achieved it, and 73% mastered it. Thus, it is concluded that the use of digital tools contributes significantly to learning, adapting to the individual needs of students. For this reason, teachers are encouraged to integrate digital tools since they can substantially improve the teaching-learning process of the Kichwa language.